Job Satisfaction of Vocational High School Teachers - Bunyamin Bunyamin (Syntax Corporation Indonesia, 2023)
The purpose of this study is to analyze the relationship between: 1) organizational climate with teacher job satisfaction, 2) commitment with teacher job satisfaction and 3) climate and commitment together with teacher job satisfaction. The research was conducted at SMK in Ciracas District, East Jakarta with a population of 362 teachers. Using the Slovin formula with an error rate of 0.05, a simple random sample of 191 teachers was taken. Test the hypothesis using a correlation test. For the measurement of job satisfaction variables, five dimensions are used: namely interest in work done with indicators (1) diligent work and (2) increasing competence. The dimensions of awards received with indicators (1) compensation and (2) promotion. The supervisor's ability dimension provides technical assistance with indicators: (1) academic supervision and (2) clinical supervision. In general, the results of the study prove that the job satisfaction of teachers working at SMK Ciracas District can be influenced by organizational climate variables and commitment variables. As for suggestions for research related to the integration model of the influence of organizational climate variables and organizational commitment to job satisfaction, it can be done in the scope of work of private organizations.